Different frequencies of Porphyromonas gingivalis infection in cancers of the upper digestive tract. (28th September 2017) - Yuan, Xiang; Liu, Yiwen; Kong, Jinyu; Gu, Bianli; Qi, Yijun; Wang, Xinshuai; Sun, Man; Chen, Pan; Sun, Wei; Wang, Huizhi; Zhou, Fuyou; Gao, Shegan
Abstract: The high incidence rate of multiple carcinomas in the upper digestive tract is often explained in terms of involvement of the same underlying risk factors. It has been reported that the oral bacterium Streptococcus anginosus is associated with esophageal, gastric, and pharyngeal cancers. We previously reported occurrence of Porphyromonas gingivalis (P. gingivalis) DNA in esophagus cancer. In this study, the presence of P. gingivalis in specimens of various types of cancer from the upper digestive tract was investigated. Here we report that P. gingivalis was preferentially and frequently present in specimens of esophageal cancer as well as in those from dysplasia of the esophagus but rarely in matched noncancerous portions and are quite low or absent in cancers from the cardia or stomach. Therefore, it led us to propose that, the microorganism does not survive in conditions of high acidity. We then investigate the pH dependence of survival of P. gingivalis as well as the acid tolerance of it. We found that, exposure to acidic buffers of a wide range of pH values led to a decline in colony forming units of P. gingivalis, thus, providing a possible explanation for variations in frequencies of P. gingivalis infection in this study.